SFMM design in colocated CS‐MIMO radar for jamming and interference joint suppression. Issue 7 (1st July 2018) - Xiong, Wei; Greco, Maria; Gini, Fulvio; Zhang, Gong; Peng, Zhenni
Abstract : This study focuses on the problem of joint suppression of active jamming in target sector‐of‐interest (SOI) and out‐of‐sector interference for colocated compressive sensing multiple‐input–multiple‐output (CS‐MIMO) radar. Three effective strategies for spatial filter measurement matrix (SFMM) design are outlined. Unlike the previous reported Capon beamformer and minimum variance distortionless response beamformer, the proposed design strategies only depend on the target spatial SOI rather than the accurate directions‐of‐arrival (DOAs) of targets, jammers and interfering sources to obtain deep nulls or notches for the SOI jamming and low‐attenuation levels for the out‐of‐sector interference. The SFMM design criteria are derived using the second‐order cone programming and solved as convex optimisation problems. The proposed approaches can simultaneously suppress the SOI jamming and attenuate the out‐of‐sector interference. Meanwhile, better DOA estimation accuracy can be achieved. Simulation results demonstrate the superiority of the proposed approaches over the other methods for colocated CS‐MIMO radar.